Patients With Syncope in a German Emergency Department: Description of Patients and Processes - Gueldner, Sebastian; Langada, Viktoria; Popp, Steffen; Heppner, Hans Jürgen; Mang, Harald; Christ, Michael (Deutsches Ärzteblatt international, 2012)
Background: We studied the characteristics and resource utilization of patients with syncope in a German emergency department (ED). Methods: We carried out a single-center retrospective analysis of patients with syncope who presented to the ED of the Klinikum Nürnberg (a municipal hospital in Nuremberg, Germany). Results: Among the 28 477 patients who presented to the ED from 15 May 2009 to 30 September 2009, 440 (1.5%) presented with syncope. Their mean age was 62 years (standard deviation, 20 years); 50.4% were women, 43.4% were over age 70, 11.8% had cardiogenic and 4.8% neurological syncope, and 18.2% had more than two comorbid conditions. 20.7% were discharged after evaluation in the ED, 14.1% were brielfly hospitalized in the ED's clinical observation unit, and 56.6% were admitted to one of the hospital's specialty wards. 8.6% left the ED against medical advice. All of the syncope patients were evaluated by history-taking, physical examination, and 12-lead electrocardiogragraphy (ECG); ECG revealed abnormal findings in 36.4% of patients. Nearly all patients also underwent laboratory testing, which revealed hyponatremia (a serum sodium concentration under 130 mmol/L) in 5.9% and a serum creatinine level above 2 mg/dL in 5.3%. Many underwent technology-intensive tests such as cranial computed tomography (129 patients), but these tests only rarely yielded abnormal findings (3.1%). 27% of the syncope patients underwent Doppler ultrasonography of the vessels supplying the brain, with abnormal findings in 6.7% of cases. (Orthostatic testing was performed in 14.5% of the patients and was positive in 26.6%.) Conclusion: Many patients presenting with syncope to a German ED are elderly, and multiple comorbidities are common. Technology-intensive testing in patients with syncope has a low diagnostic yield and consumes resources. The introduction of standards for the evaluation of syncope in the ED would be helpful.
CRIS-Team Scopus Importer:2022-09-26